Development of a method for determining the morpholinium thiazotate using more economic and green GC/MS assay with an fid detector - Belikova, A.; Materienko, A.; Sidorenko, L.; Chornyi, V.; Korzh, I.; Kucherenko, L. I.; Kotvitska, A.; Burdulis, D.; Georgiyants, V.; Кучеренкоб Людмила Іванівна (My University, 2022)
One of the main steps in the pharmaceutical development of drugs is the choice of quality control methods. The correctness of the method must be confirmed by validation. In addition, manufacturers take into account various economic and environmental factors. It is especially important to determine the above aspects for domestic and promising drugs, such as the morpholinium thiazotate. The aim. During the development of methods for the routine analysis of medicinal products, attention should be paid to efficiency of analysis, budget, as well as their impact to the environment. Because of this reason, not only new methods for routine analysis should be developed. It is important this methods must be environmentally-friendly and cost-efficient. Materials and methods. The determination of the morpholinium thiazotate was carried out by HPLC using the SunFire C18 (150×4.6 mm, 5.0 μm) and gas chromatography with a flame ionization detector using the Rxi-5 ms (30 m long, 0.25 mm outer diameter and 0.25 μm liquid stationary phase thickness). Results. Various chromatographic methods for the routine quantitative analysis of morpholinium thiazotate were developed. The most suitable conditions for sample preparation were established. Proposed methods were compared to find the most ecological and economic. Conclusions. Proposed methods were accurate and reliable. However, an environmental impact assessment showed that GC-FID is a more environmentally friendly and economical method of analysis. Using 12 Principles of green analytical chemistry, the overall “analytical GREEnness (AGREE)” scale for the proposed analytical approach was computed 0.72, showing the good greener nature of the proposed analytical approach
Keywords: HPLC; GC-FID; method development; analytical eco-scale; cost analysis; environmental; AGREE scale